Seismic isolation of rigid cylindrical tanks using friction pendulum bearings. - Wang, Yen-Po (Earthquake engineering & structural dynamics.)
Storage tanks are vulnerable to earthquakes, as numerous major earthquakes have demonstrated. The trend of recent revisions to make seismic design criteria for large scale industrial storage tanks increasingly stringent has made development of cost effective earthquake resistant design and retrofit techniques for industrial tanks imperative. This study assesses the feasibility of seismic base isolation for making liquid filled storage tanks earthquake resistant. The sliding type friction pendulum seismic (FPS) bearings are considered rather than the elastomeric bearings because the dynamic characteristics of an FPS isolated tank remain unchanged regardless of the storage level. This work has devised a hybrid structural hydrodynamic model and solution algorithm, which would permit simple, accurate and efficient assessment of the seismic response of rigid cylindrical storage tanks in the context of seismic isolation. Extensive numerical simulations confirm the effectiveness of seismic base isolation of rigid cylindrical tanks using FPS bearings.